Social Media Content Marketing and Purchase Intention: An Analysis of the Mediating Role of Tourists’ Emotional Engagement in MSME Products - Faisal Rizal Zaenal; Fitriani Latief (Jurnal Economic Resource, 2026)
The purpose of this study is to analyze: (1) the direct effects of social media content marketing on emotional engagement, perceived informativeness, and purchase intention; (2) the direct effects of emotional engagement and perceived informativeness on purchase intention; and (3) the indirect effect of social media content marketing on purchase intention through the two mediating variables. This study employed a quantitative approach. Data were collected through questionnaires distributed to 200 domestic tourists purchasing MSME products in Tana Toraja and North Toraja. The sample was determined using purposive sampling based on specific criteria. Data analysis was conducted using Structural Equation Modeling (SEM) with AMOS software to examine the relationships among variables. The findings reveal that social media content marketing significantly enhances both emotional engagement and perceived informativeness but does not directly influence purchase intention. Conversely, emotional engagement positively and significantly affects purchase intention, whereas perceived informativeness shows no significant direct effect. The mediation analysis indicates that emotional engagement serves as a significant mediator in linking social media content marketing to tourists’ purchase intention, whereas perceived informativeness, although positive, fails to mediate.